Speechless - Steinke, Aron Nels (Graphix, an imprint of Scholastic, 2025)
Middle school was supposed to be a fresh start for Mira, who struggles to speak in class even though she can speak at home without a problem. Her former best friend, Chloe, has become her worst enemy, and Mira's only solace is making videos for her secret stop-motion animation channel. But when Chloe's mom has to travel for a family emergency, Mira is horrified to learn that her family has volunteered to let Chloe stay with them. When it feels like everything is going wrong, will Mira ever find her voice?